Contribution of the second stage of labour to pelvic floor dysfunction: a prospective cohort comparison of nulliparous women. (19th February 2014) - Rogers, RG; Leeman, LM; Borders, N; Qualls, C; Fullilove, AM; Teaf, D; Hall, RJ; Bedrick, E; Albers, LL
<x xml:space="preserve">Abstract</x> Objective Maternal expulsive efforts are thought to damage the pelvic floor. We aimed to compare pelvic floor function and anatomy between women who delivered vaginally (VB) versus those with caesarean delivery (CD) prior to the second stage of labour. Design Prospective cohort. Setting University Hospital Midwifery practice. Population Nulliparas. Methods Pregnant nulliparas were recruited during pregnancy and women who underwent CD prior to the 2nd stage of labour at birth were recruited immediately postpartum. Both groups were followed prospectively to 6 months postpartum. Main outcome measures POPQ, perineal ultrasound (U/S) and Paper Towel Test (PTT), an objective measure of stress incontinence; Incontinence Severity Index (ISI), Pelvic Floor Impact Questionnaire (PFIQ‐7), Wexner Fecal Incontinence Scale (W) and Female Sexual Function Index (FSFI). Results 336/448 (75%) VB and 138/224 (62%) CD followed up. The VB group was younger (23.9 ± 4.9 versus 26.6 ± 6.1 years, P < 0.001) and less overweight/obese (38 versus 56%, P < 0.001); baseline functional measures were similar (all P > 0.05). At follow‐up, urinary incontinence (UI) (55 versus 46% ISI > 0, P = 0.10), fecal incontinence (FI) (8 versus 13% FI on W, P = 0.12), sexual activity rates (88 versus 92%, P = 0.18) and PFIQ‐seven scores were similar. Positive PTT tests (17 versus 6%, P = 0.002) and ≥ Stage 2 prolapse (22 versus 15%, P = 0.03) were higher with VB; differences were limited to points Aa and Ba. U/S findings were not different between groups. Stepwise multivariate analyses controlling for age, body mass index, and non‐Hispanic White race for prolapse of points Aa and Ba did not alter conclusions (all P < 0.004). Conclusions VB resulted in prolapse changes and objective UI but not in increased self‐report pelvic floor dysfunction at 6 months postpartum compared with women who delivered by CD prior to the second stage of labour. The second stage of labour had a modest effect on postpartum pelvic floor function.